Effect of total dissolved salts (TDS) in drinking water of poultry on some veterinary drugs concentration (Journal of Hama University, 2022)
Abstract:The study was conducted to evaluate the effect of different concentrations of dissolved salts in drinking water used in poultry on the concentration of doxycycline (50% powder) and enrofloxacin (10% liquid) after mixing them with therapeutic dose recommended by the company  (0.2 g doxycycline and 0.5 ml of enrofloxacin/liter of drinking water).Six levels of dissolved salts in water, ranging between 311 and 11700 mg/L, were used in this study, and they were compared with distilled water. High-performance liquid chromatography technique was used to evaluate the concentration of doxycycline using a mobile phase consisting of oxalic acid, methanol, and acetonitrile, with mixing ratios, respectively (60/10/30), wavelength 350 nm, reversible phase column C8, and a flow rate of 1 ml/min. For Enrofloxacin, a mobile phase resulting from mixing  of water, acetonitrile, and triethylamine was used, (80/19/1) (pH = 3), wavelength of 278 nm, and a reversible phase column C18 type and  flow rate of 1ml/min.The results indicate that there is an effect of the level of dissolved salts on the concentration of doxycycline and enrofloxacin, as there was a gradual decrease in the concentration of the two compounds with the increase in the concentration of dissolved salts in water. Decreasing percentage of doxycyclie amd enrofloxacin in the wtaer with highest TDS (11700 mg/L) were 18.3 and 25.92%, respectively, and the differences in the mean concentrations of doxycycline and enrofloxacin in all studied water samples were significantly different (P